Avaliação da pesca da lagosta vermelha (Panulirus argus) e da lagosta verde (Panulirus laevicauda) na plataforma continental do Brasil. - Barroso, Juarez Coelho (2012)
Extractive fishing lobster in Brazil is an important economic activity which includes different social sectors in the coastal region and provides an average annual income of USD$ 84 million. The great demand for the product, the high value in international market, expansion of the artisanal fleet, failure in enforce of conservation measures, the fishing impact on ecosystems and perhaps climate variability, have led to a high exploitation or overexploitation of the crustacean stocks. The evaluation and fishery prediction depends of biological and fisheries data collection, in the last two decades the absence of these data and the lack in the life cycle study generated a high level of uncertainty in the management of the fishery. In the present study, a comprehensive analysis is done of biological and fishery information generated by the thesis project and the data that precedes. The areas of the stock aggregation were distributed into 31 strata covering an area of 356.610 km2, divided into two regions: shallow < 50 m (160.510 km2) and depth between 50 and 100 m (196.100 km2). The medium productivity index (1999-2006) between species was 29,75 kg/km2 in Panulirus argus and 8,39 kg/km2 in P. laevicauda; in different strata varied between 0.02 and 217.0 kg/km2 (both species). Catchability coefficients ranged between 0.10 and 0.14, showing that the fishing gears (caçoeira, manzuá and cangalha) have a low efficiency in the lobster fishery. The sampling of landings between different fishing periods (1970-1979, 1980-1988 and 1989- 1993) showed a progressive decrease in the small lobsters and as a result the mean length showed an increasing trend. The random samples on boats that fished between 20 and 35 m (1999), revealed that lobsters recruited (50 and 75 mm, Lc) accounted for 91% (P. argus) and 96% (P. laevicauda) of the total catch, which with the expansion of fishing (increased effort) was accompanied by a decreasing of the CPUE by fishing grids (between 1974 and 1991), showed a growth overfishing which are probably influencing in the high variations of the annual catches and its negative trend observed in the last fifteen years (1995-2009). The analysis between CPUE and abundance (N), revealed a lack of proportionality (hyperstability) between both parameters, which could be affecting the relationship between CPUE and effort and overestimating yield maximum sustainable (YMS). We estimated a yield maximum sustainable per unit area of 14 kg/km2 and a yield maximum sustainable preliminary between 5,000 and 5,604 t. This empirical result should be confirmed through the development of stratified random sampling is proposed in this study. There is not evidence of recruitment overfishing in the stocks, but high rates of exploitation in the deep stock (50 to 100 m) of P. argus, composed mainly of older specimens and high reproductive power, could be accentuating the risk of low recruitment and collapse. This high level of uncertainty which takes the lobster fishery on the continental shelf of Brazil must be addressed by new ways of thinking, by a long-term and acquiring new skills and knowledge to develop fisheries sustainable.